Chironomidae fauna of springs in Iceland: Assessing the ecological relevance behind Tuxen’s spring classification - Agnes-Katharina Kreiling; Jón S. Ólafsson; Snæbjörn Pálsson; Bjarni K. Kristjánsson (Journal of Limnology, 2018)
In 1937, S.L. Tuxen studied the animal community of hot springs in Iceland, and classified springs according to their relative temperature into cold, tepid, and hot. Eighty years after Tuxen’s study, we revisited some of the hot springs in Skagafjörður, Northern Iceland. Our aim was to compare the invertebrate community of 1937 and today, and to assess the stability of hot spring habitats over the years. To test Tuxen’s spring classification on an ecological basis, we furthermore collected chironomid larvae from 24 springs of a broad range of temperature, with samples taken both at the surface area of the spring and at the groundwater level. The chironomid species composition of hot springs differed from that of cold and tepid springs. Whereas Cricotopus sylvestris, Arctopelopia sp., and Procladius sp. characterised the chironomid community in Icelandic hot springs, cold and tepid springs were dominated by Eukiefferiella minor, Orthocladius frigidus and Diamesa spp. Community composition analyses and the exclusive occurrence of taxa in one of the temperature classes validated the ecological relevance of Tuxen’s spring classification for the chironomid species community. Both environmental parameters and invertebrate community of Icelandic hot springs seem to be the same as 80 years ago. Although springs have the potential to provide stable habitats, they are currently under high anthropogenic pressure, and should be increasingly considered in nature conservation.